2022
DOI: 10.21744/lingcure.v6ns2.2134
|View full text |Cite
|
Sign up to set email alerts
|

Developing a guided discovery model based on reflective teaching to improve students' short essay writing skills

Abstract: This research is motivated because there is no essay writing model in learning English. Lecturers have not applied the Reflective teaching approach in learning in their classrooms. This has an impact on students' ability to write short essays in learning English. This study aims to develop a Reflective Teaching-Based Guided Discovery Model to Improve Students' Short Essay Writing Skills. The method used in this research is Research and Development using the ADDIE Model. The result of expert validation of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, employing Peer Assessment Technique is considered by students as a useful technique in terms of helping them understand the common errors they make in sentence writing as proposed by Abbas & Herdi (2018) and Afriani (2018) as well as how to formulate a correct sentence grammatically (Indasari et al, 2019;Mumpuni et al, 2022;Rizky & Zainil, 2021). By including fellow peers in assessing the quality of their writing, students can receive constructive feedback, identify weaknesses in sentence structure and grammar, and ultimately improve their writing skills significantly (Ayu et al, 2022;Haeriyati et al, 2023;Mantra et al, 2020;Meletiadou, 2021& Rahma et al, 2023.…”
Section: Effective Impact Of the Peer Assessment Technique On Student...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, employing Peer Assessment Technique is considered by students as a useful technique in terms of helping them understand the common errors they make in sentence writing as proposed by Abbas & Herdi (2018) and Afriani (2018) as well as how to formulate a correct sentence grammatically (Indasari et al, 2019;Mumpuni et al, 2022;Rizky & Zainil, 2021). By including fellow peers in assessing the quality of their writing, students can receive constructive feedback, identify weaknesses in sentence structure and grammar, and ultimately improve their writing skills significantly (Ayu et al, 2022;Haeriyati et al, 2023;Mantra et al, 2020;Meletiadou, 2021& Rahma et al, 2023.…”
Section: Effective Impact Of the Peer Assessment Technique On Student...mentioning
confidence: 99%
“…Previous research on Peer Assessment Technique in teaching writing has revealed important findings. Yet, numerous research discovered by (Ayu et al, 2022;Haeriyati et al, 2023;Indasari et al, 2019;Mantra et al, 2020& Mumpuni et al, 2022 discovered that the Peer Assessment Technique can improve the quality of students' writing. Through Peer Assessment Technique, students can receive more diverse and in-depth feedback on the quality of their writing, which may not be possible through teacher assessment alone (Indasari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One key factor influencing instructors’ life-long professional growth and psychological well-being is reflection [ 6 , 7 ]. As a salient component of professional development and education, reflective teaching is believed to promote the professional competence of lecturers and teachers [ [8] , [9] , [10] ]. Reflective teaching is considered as a crucial process in teacher education and has been widely discussed and researched in the educational literature [ [11] , [12] , [13] ] after the introduction of reflective practice by John Dewey [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Communication will not go well without sufficient vocabulary. In the opinion of to (Ayu et al, 2022) many students get lazy due to the extensive foreign vocabulary and sentence patterns that differ from Indonesian. This fear then makes them dislike English.…”
Section: Introductionmentioning
confidence: 99%